The Multimodal Portrayal of The 2019 Indonesian Presidential Candidates' Rivalry on English Tempo's Cover Stories - Zakie Asidiky (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
This research has investigated how English Tempo magazine's cover stories portrayed the Indonesian presidential candidate's rivalry between Joko Widodo (Jokowi) and Prabowo Subianto (Prabowo) to audiences. Four English Tempo's cover stories were then selected as the data and analyzed by the Multimodal Discourse Analysis (MDA) approach. Furthermore, this research uses a qualitative method with descriptive perspective for data analysis. Moreover, the results have shown that (i) the presidential and vice-presidential candidates' photographs and caricatures, (ii) the illustrations of presidential candidates' actions related to specific political events at the time, and (iii) the main titles could multimodally portray the presidential candidates' rivalry to the audiences. The photographs and caricatures in the cover stories' pictorial components visually manifested the candidates' rivalry. Moreover, the cover stories' main titles explained the photographs and caricatures. Furthermore, those semiotic components combined in each cover story could modulate some multimodal communicative acts to portray the rivalry between presidential candidates. Meanwhile, the benefit of this research result is to provide the readers with the formulation of how English Tempo Magazine presents the topic of rivalry between Indonesian presidential candidates by visualizing issues concerning presidential candidates in the cover stories.